World Economic and Social Survey 2004 - United Nations (United Nations, 2004)
The 2004 edition of the World Economic and Social Survey is divided into two parts. The first part discusses the state of the world economy in 2004 and the outlook for 2005. It includes a review of developments in international trade and finance and an overview of the situation in the world’s economies as of mid-2004 and their prospects for 2005. Meanwhile, the second part addresses international migration. It examines historical and recent surges in migration, policies towards migration, its economic and social effects, the question of refugees and the state of international cooperation regarding migration.